RANCANG BANGUN APLIKASI GAME MULTIPLAYER SEBAGAI ALAT BANTU PROSES PEMBELAJARAN BERBASIS WEBSOCKET - Aryo Wibowo, Mohammad; Arsa Suyadnya, I Made; Oka Saputra, Komang (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p15, 2021)
The development of technology information is growing rapidly. For example in the education world, the purpose of interactive learning media is increasingly felt. With that purpose, an ICT-based learning process (Information Communication Technology) can be developed which has the concept of computer and multimedia learning. Computers can be used as a substitute for books and also multimedia can be used as a substitute for teachers when explaining the material. In this study, to give an innovation in the learning models that use quizzes in the learning process, so it would be build a plan of a web socket based of multiplayer game application as a tool for learning process. To making this system, the advantage of web socket is to give a speed in exchanging information on the game system. Finally, the result of this application are to produce a web socket based of multiplayer game system design and how web sockets work when used in a game. The results of the research produce a system design game multiplayer based websocket. Based on BlackBox Testing and websocket testing. the basic needs of the game are functionally fulfilled and the use of the system websocket provides a shorter lag time for requests and responses.